Da prosa dos objetos cotidianos à poética dos objetos artísticos: por uma estética do cotidiano - Costa Filho, José Almir Valente (2016)
This work investigates some contemporary artistic manifestations which bring in their aesthetic experiences objects made from items of everyday life that, through various operations, are transformed into contemporary visual poetics. It analyses aesthetic changes in the status of art which have occurred from modern and contemporary art with the emergence of Duchamp's ready-mades, going through Arman's assemblages, performances and happenings of Fluxus artists until the contemporary installations of El Anatsui. The strategies of the processes of production, assembly/exhibition and apprehension of those works are also brought into appreciation. As a corpus of analysis, three works were selected: Manto da apresentação (Mantle of Presentation) (1985) by Arthur Bispo do Rosário, Arqueologia poética (Poetic Archeology) (2011) by Luiz Antônio Rodrigues - Chiquitão and Marat (Sebastião) (2009) by Vik Muniz. Fundamentally, the choice of these works was based on their original aspect. Their singularity comes from the fact that those artists use materials and objects of daily use as one of the elements that constitute the materiality of the aesthetic arrangement of their works, in relation to other art materials. The theoretical and methodological basis of this work is found in the French semiotics of Algirdas Julien Greimas, with its developments in Plastic semiotics, in the researches of Jean-Marie Floch and Ana Claudia de Oliveira, as well as in the works of Eric Landowski about the “sense felt" in constituting acts produced from interaction regimes. Throughout the analysis of the corpus, it can be noticed how is produced the construction of meaning concerning these different discourses, as well as of the interactions coming from the relationship between enunciator and enunciatee. Thus, it is demonstrated, at this point, how matter and materials mean in the aesthetic discursive construction of the works and in the aesthesia condition of the production of the sense that gives meaning to it. The focus of the semiotic on the sensitive matter of art, makes it possible to establish a more in-depth study of the issues listed here. It can be better realized that the formants of matter have a special "force" - during the creation of high impact discourses towards the art spectators and, in their context, being able to engage them in the works that promote aesthesia and which materiality is the outlet that affects them. This sensitizes the artists to the new uses of matter and materials, re-signifying their use in everyday life, an achievement of the art produced in Brazil in dialogue with other international artistic trends